Dziecko w środowisku pieniądza: przekonania podzielane przez dzieci w wieku 8–9 lat - Renata Raszka (Problemy Wczesnej Edukacji)
This article is a report from qualitative research conducted by the text’s author. Third grade primary school pupils who took part in the study have expressed their view of money by completing twelve incomplete sentences about money. The aim of the study was to find children’s shared beliefs about money. In accordance with the instrumental and symbolic nature of money there appear to be two main groups of phrases ending incomplete sentences. Some of children’s statements refer to instrumental understanding of money, that is, they relate to its value in use and economic functions. Other statements are connected with the symbolic nature of money, showing its psychological and social functions.